Community in Speed Space: Media Information About Ulumbu PLTP Geothermal - Franciska Anggelli , Tefbana; Bonar, Situmorang (Journal of Sumatera Sociological Indicators, 2024)
Digitalization has caused the images of time and space to blur. The rapid flow of mediated information causes confusion and a lack of humanitarian awareness. This paper explains the reality of the Poco Leok case in the construction and expansion of the PLTP Ulumbu. Using Dromology theory by Paul Virilio in "Speed and Politics" with a qualitative approach. The Poco Leok case is often based on media narratives that state that the expansion of the PLTP Ulumbu is for the benefit of common welfare, but in reality, the expansion of the PLTP Ulumbu sacrifices and torments the people through land-greedy investments with iron fist regimes, domination of power, and neglect of people's voices in the public sphere. The media in the PLTP Ulumbu case succeeded in polarizing the community based on their interests and making the community the subject of receiving geothermal potential that must be managed.